GASTROINTESTINAL INDEX OF LIFE QUALITY OF PATIENTS AFTER ESOPHAGOPLASTY - I. E. Sudovykh (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
After one-stage transhiatal esophagoplasty more than 1 year ago for benign esophageal diseases GIQLI questionnaire was completed by 30 patients after esophageal extirpation with gastric tube esophagoplasty and 25 patients after bypassing esophagoplasty with left colon. Based on type of esophagoplasty and. follow-up period. (1-3 years, 3 and. more years) patients were divided up into 4 groups. Statistic analysis revealed evidently (p